(untitled) (Modern American Journal of Biological and Environmental Sciences, 2026)
This article presents the evaluation results of major yield-related agronomic traits in introduced quinoa (Chenopodium quinoa Willd.) variety samples under the agroecological conditions of Uzbekistan. The experiment was conducted at the experimental farm of the Tashkent State Agrarian University using a randomized design with three replications. Important agronomic traits including plant height, panicle characteristics, wet and dry panicle weight, 1000-seed weight, and yield performance were analyzed. The obtained results revealed significant genotypic variability among the studied variety samples. Several quinoa samples demonstrated superior productivity, biomass accumulation, and better adaptability to local environmental conditions. The findings provide an important scientific basis for the selection of promising quinoa germplasm and the development of breeding materials for future quinoa improvement programs.